2021
DOI: 10.3390/nu13114175
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Vitamin D Deficiency in 9595 Mongolian Schoolchildren: A Cross-Sectional Study

Abstract: Population-based data relating to vitamin D status of children in Northeast Asia are lacking. We conducted a cross-sectional study to determine the prevalence and determinants of vitamin D deficiency in 9595 schoolchildren aged 6–13 years in Ulaanbaatar (UB), the capital city of Mongolia. Risk factors for vitamin D deficiency were collected by questionnaire, and serum 25-hydroxyvitamin D (25[OH]D) concentrations were measured using an enzyme-linked fluorescent assay, standardized and categorized as deficient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…32–35 Our finding of a small borderline-significant positive effect of vitamin D supplementation on long jump distance supports the concept that vitamin D has a physiological role in supporting muscle strength. 5 However, the fact that this was not associated with an effect on grip strength, plus the observation that no such effect was seen in Mongolian children (who had a significantly higher baseline prevalence of vitamin D deficiency than participants in the current study) 10 11 suggests that this result may have arisen as a result of type 1 error arising as a result of investigating multiple secondary outcomes. The other borderline-significant finding was in the opposite direction to that anticipated: vitamin D supplementation associated with an increased risk of EIB at 3-year follow-up, in contrast to expectations that the intervention would reduce this risk via its immunoregulatory actions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…32–35 Our finding of a small borderline-significant positive effect of vitamin D supplementation on long jump distance supports the concept that vitamin D has a physiological role in supporting muscle strength. 5 However, the fact that this was not associated with an effect on grip strength, plus the observation that no such effect was seen in Mongolian children (who had a significantly higher baseline prevalence of vitamin D deficiency than participants in the current study) 10 11 suggests that this result may have arisen as a result of type 1 error arising as a result of investigating multiple secondary outcomes. The other borderline-significant finding was in the opposite direction to that anticipated: vitamin D supplementation associated with an increased risk of EIB at 3-year follow-up, in contrast to expectations that the intervention would reduce this risk via its immunoregulatory actions.…”
Section: Discussionmentioning
confidence: 58%
“…[5][6][7] Deficiency in this fat-soluble micronutrient -indicated by low circulating concentrations of 25-hydroxyvitamin D (25[OH]D) -is widespread among children in both higher-and lower-income countries. [8][9][10][11] Observational studies have linked vitamin D deficiency in children and adolescents to reduced muscle strength and cardiorespiratory fitness, 12 13 and increased risk of exercise induced bronchoconstriction (EIB), 14 which may limit exercise capacity. Numerous randomised controlled trials (RCTs) in adults have revealed positive effects of vitamin D supplementation on muscle strength and power, with meta-analyses reporting a modest benefit overall.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, inflammatory status of individuals cannot be evaluated comprehensively. Moreover, a caution should be taken when interpreting this study results, since previous studies (32)(33)(34)(35)(36)(37) have shown that components of the CVR score in this study (BMI, blood pressure, total cholesterol, glucose levels, and smoking status, and also triglyceride levels) are in inverse association with vitamin D levels, and therefore, a higher CVR score should be automatically associated with lower vitamin D levels in our study. To sum, our research was conducted only on the pregnant Chinese women.…”
Section: Study Limitationsmentioning
confidence: 72%
“…Although sun exposure and vitamin D may have independent risk factors for CNS demyelination [ 63 ], a recent meta-analysis reported [ 64 ] a significant association between low vitamin D and increased risk of developing MS. Although a high prevalence of vitamin D deficiency has been reported in Mongolia [ 65 ], serum vitamin D levels in MS patients were not performed in our current study.…”
Section: Discussionmentioning
confidence: 98%